The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1744-7909.2010.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Rice Metallothionein Gene Promoter: Its Tissue Specificity and Heavy Metal Responsiveness

Abstract: The rice (Oryza sativa L.) metallothionein gene OsMT-I-4b has previously been identified as a type I MT gene. To elucidate the regulatory mechanism involved in its tissue specificity and abiotic induction, we isolated a 1 730 bp fragment of the OsMT-I-4b promoter region. Histochemical β-glucuronidase (GUS) staining indicated a precise spacial and temporal expression pattern in transgenic Arabidopsis. Higher GUS activity was detected in the roots and the buds of flower stigmas, and relatively lower GUS staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 49 publications
(59 reference statements)
1
10
0
Order By: Relevance
“…Similar to the MRE of animal MT genes, several plant MREs are responsible for heavy metal-induced expression of reporter gene (Lü et al, 2007;Qi et al, 2007a;Dong et al, 2010). This indicates that MRE is a highly conserved MRE among plants and animals.…”
Section: Pvmtf-1 Is a New Mre-binding Transcription Factor In Plantsmentioning
confidence: 84%
See 2 more Smart Citations
“…Similar to the MRE of animal MT genes, several plant MREs are responsible for heavy metal-induced expression of reporter gene (Lü et al, 2007;Qi et al, 2007a;Dong et al, 2010). This indicates that MRE is a highly conserved MRE among plants and animals.…”
Section: Pvmtf-1 Is a New Mre-binding Transcription Factor In Plantsmentioning
confidence: 84%
“…Interestingly, MRE also exists in the promoter regions of many Cd-responsive plant genes, such as Pseudotsuga menziesii metallothionein-like gene (PmMT; Chatthai et al, 2004), rice (Oryza sativa) metallothionein gene (ricMT; Lü et al, 2007), rice class I-4b metallothionein gene (OsMT-I-4b; Dong et al, 2010), and bean (Phaseolus vulgaris) stress-related gene2 (PvSR2; Qi et al, 2007a). Moreover, in rice, many Cd-responsive miRNA-encoding genes contain MREs in their promoters (Ding et al, 2011), suggesting that MREs may also be involved in Cdinduced transcription of noncoding genes in plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast functional complementation assays revealed that the expression of MT1a , MT2a and MT3a genes in Arabidopsis could increase the tolerance of yeast mutants to Cu and Cd [39], [40], [41]. However, with regard to Pb, little is known about the relationship between the induction of plant MT genes and lead tolerance [42], [43], [44]. It is also the same for phytochelatin that were identified as heavy metal-binding peptides involved in the accumulation, detoxification and metabolism of metal ions (for review [18]).…”
Section: Discussionmentioning
confidence: 99%
“…(C) Selected promoter fragments of lëjqNÇ (top). ChIP analysis was performed of the lëjqNÇ promoter using chroma-heavy metals, such as Cu² + , Pb² + and Al³ + (Dong et al, 2010). It would be therefore interesting to determine whether the W box element at -729~-724, defined as the OsWRKY42 binding site in our present study and located in the interval of the important lëjqNÇ promoter region, can also participate in the regulatory response to heavy metals.…”
Section: Discussionmentioning
confidence: 99%